Mid-infrared tunable intracavity singly resonant optical parametric oscillator based on Mgo : PPLN - Zhang, Jing (2018)
In this paper, we demonstrated a continuous-wave intracavity singly resonant optical parametric oscillator based on periodically poled MgO:LiNbO3 (MgO:PPLN) pumped by a diode-pumped Nd:YVO4 laser at 1064 nm. The singly resonant optical parametric oscillator only outputs the idler light as its cavity high reflectivity was coated at the signal light. When the temperature was controlled at 120°C and the grating period set at 30.5 μm for the MgO:PPLN, a maximum idler output power of 1.27 W and central wavelength at 3251 nm were obtained under an incident diode pump power of 12.4 W, corresponding to the conversion efficiency of 10.2%. By changing the temperature and the grating period of MgO:PPLN crystal, widely tunable mid-infrared spectra from 2.95 to 4.16 μm were achieved.